Star of the North [compact disc, unabridged] : a novel - John, David, 1966- (Random House Audio, 2018)
A propulsive and ambitious thriller about a woman trying to rescue her twin sister from captivity in North Korea, and the North Korean citizens with whom she forms an unlikely alliance.